(untitled) (Dhaka University Journal of Biological Sciences, 2023)
In Bangladesh, antibiotics are given to animals in order to improve their health and productivity. This can, however, lead to development of antibiotic resistance in the bacteria and subsequent transfer of the resistance property to human. Twenty one bacteria were isolated from five livestock fecal samples collected from Chankharpul, Sadarghat and Savar. Seven of the most commonly used antibiotics (Streptomycin, Chloramphenicol, Ciprofloxacin, Azithromycin, Oxytetracycline, Co-trimoxazole and Erythromycin) in animal feed in Bangladesh were tested. All (100%) the isolates were sensitive to Chloramphenicol and Tetracycline. Highest resistance was shown to Oxacillin (52.38%) followed by Erythromycin (33.33%) and Streptomycin (33.33%), Azithromycin (23.81%), Oxytetracycline (19.05%) and Ciprofloxacin (19.05%) and finally Co-trimomoxazole (14.29%). Four (19%, n = 21) of the bacteria were resistant to three or more antibiotics and were hence multidrug resistant. All isolates from Chankharpul were resistant to Streptomycin, Erythromycin and Oxacillin whereas all were sensitive to Chloramphenicol and Tetracycline. In case of Sadarghat, highest resistance (67%) was shown to Azithromycin and least (0 %) to Oxytetracycline, Streptomycin and Tetracycline. Isolates from Savar showed highest resistance (87.5%) to Oxacillin and all were sensitive to Chloramphenicol. Based on the findings of this study, we recommend the use of Chloramphenicol and Tetracycline for the treatment of livestock. High resistance to Streptomycin, Erythromycin, Oxacillin and Azithromycin suggests that the use of these antibiotics must be restricted in animal feed. Dhaka Univ. J. Biol. Sci. 32(2): 265-269, 2023 (July)